Sustainable System for TVET Teacher Education Program in Malaysia: : Fuzzy Delphi Method - Hamdan, Nor Hidayah; Md. Yunos, Jailani; Lai, Chee Sern (Online Journal for TVET Practitioners, 2020)
The purpose of this paper is to obtain an expert consensus on the criteria of a sustainable system for the TVET Teacher Education program in Malaysia. The sustainable system for TVET Teacher Education program in Malaysia involves item related to the three main systems identified in the previous phase, namely program system, management system, and support system. Nine experts from three leading players in TVET Teacher Education program, which is the TVET Teacher Education institution, the government and the industry was chosen to do the verification through a questionnaire containing 25 items. The consensus from the experts was further analyzed using the Fuzzy Delphi Method. The study found that expert consensus on the criteria for a sustainable system of TVET Teacher Education program is more than 75% with a total of 24 items having a threshold value (d) â‰¤ 0.2. The items were then sorted by priority, referring to the Fuzzy Score of each item based on the Defuzzification process. Overall, the sustainable system of TVET teacher education program will influence the quality of TVET Teacher Education graduates, which is the TVET teacher who will contribute to the quality of TVET workers in the future. Therefore, all players need to work together towards the sustainability of the program.